Minimally Invasive Microneedle Array Electrodes Employing Direct Electron Transfer Type Glucose Dehydrogenase for the Development of Continuous Glucose Monitoring Sensors. (2017) - Sharma, Sanjiv; Takagi, Eri; Cass, Tony; Tsugawa, Wakako; Sode, Koji
Abstract: Closed loop systems hinge on the accuracy and precision of the continuous glucose monitoring sensors. Most of the commercially available continuous glucose monitoring sensors is implanted subcutaneously for a period of 7-14 days. The subsequent biofouling effects have implications on the performance of the sensors over time especially at low glucose concentrations. In addition, the commercially available sensors are sensitive to the presence of interfering species such as acetaminophen in the skin compartment. We report here on the marriage of minimally invasive, continuous glucose sensors and a direct electron transfer type glucose dehydrogenase enzymatic system. Whilst the microneedles here are designed to sit in the dermal interstitial fluid over a 24-48 hour period to minimize the biofouling effect, the direct electron transfer enzyme allows operation of the electrochemical sensor at lower potentials to minimize the effect of interference. The microneedle structure design also enables the use of compensation electrodes for background subtraction to further nullify the effects of interference.